A Comparative Study of English and Javanese Sound Inventories - Adhi Kusuma; Victa Sari Dwi Kurniati (Universitas Sarjanawiyata Tamansiswa, 2020)
This essay aims at comparing and contrasting the English and Javanese with respect to the sound inventories completed. Based on Maddiesonâ€™s research (cited in Aronoff & Ress-Miller 2003, p. 183) there are between six and 95 consonants and between three and 46 vowels in a language. While English has 24 consonants and 12 vowels (Fromkin et al. 2008, p. 216) and Javanese has 23 consonants and 6 vowels (Ager 2009; Wedhawati & Arifin 2006, p. 65).Â In sum, the sound the English and Javanese inventories are both similar and different in several respects to how their consonants and vowels are produced and where in the mouth they are produced. Additionally, by comparing two languages, it can be seen that some sounds exist in one language but does not exist in another.Â